Fall prevalence in people with multiple sclerosis who use wheelchairs and scooters. Issue 35 (September 2017) - Rice, Laura; Kalron, Alon; Berkowitz, Shani H.; Backus, Deborah; Sosnoff, Jacob J.
Abstract : Abstract: Falls are a serious health concern for persons with multiple sclerosis (PwMS) who use wheelchairs or scooters as their primary mode of mobility. Unfortunately, little is known about the fall prevalence and characteristics of this large segment of the multiple sclerosis (MS) community. The purpose of this study is to determine the prevalence and circumstances of falls in wheelchair and scooter users living with MS. Forty-four PwMS were recruited from research and medical centers in the United States and Asia. Participants completed a survey focusing on prevalence of falls, frequency of injurious falls, circumstances of the fall, and various quality of life indicators. A total of 44 individuals (32 females/11 males/1 not reported) aged 27 to 82 years (mean = 58 yrs) completed the survey. Seventy-five percent (n = 33) reported falling at least once in 6 months and 48% (n = 12) of those that fell sustained an injury. The majority (87.5%) of the falls occurred inside the home. Most individuals (76.7%; n = 33) reported concerns about falling and 65.9% (n = 29) limited their activities because of their concern of falling. Falls are prevalent in wheelchair and scooter users with MS. The observations highlight the need for interventions targeting this segment of the MS community. Abstract : Supplemental Digital Content is available in the text